Government size, civic capital and economic performance: An O-ring approach - Luciano Mauro; Francesco Pigliaru; Gaetano Carmeci (Fondazione Eni Enrico Mattei (FEEM), 2025)
This paper explores how civic capital shapes the relationship between government size and economic performance. Building on an exogenousgrowth version of Barro (1990), we incorporate O-ring technology to capture task complementarity in the public sector, highlighting the role of civic capital in reducing errors and malfeasance. Our model shows that greater civicness not only raises the inverted U-shaped relationship between government size and output but also shifts it rightward, increasing both economic performance and the optimal government size. We test these implications using a dynamic panel data model for 23 OECD countries from 1975 to 2010, estimated via system GMM. Our results support the hypothesized inverted-U relationship and demonstrate that civic capital significantly raises the threshold at which the marginal returns to government size approach zero. Thus, countries with higher civicness can sustain larger public sectors without compromising growth. This finding provides fresh insights into how deeply institutional quality, rooted in social trust, shapes the government-size-growth nexus.
Keywords: O43; E02; H11; H21; 330; Social capital; Government size; O-ring theory; Economic growth